CBMT-25. THE KLF4K409Q MUTATION IN MENINGIOMA IMPAIRS HIF-1Α DEGRADATION AND CAN BE HARNESSED FOR TARGETED THERAPY. (11th November 2019) - von Spreckelsen, Niklas; Waldt, Natalie; Poetschke, Rebecca; Kesseler, Christoph; Dohmen, Hildegard; Jiao, Hui-Ke; Nemeth, Attila; Deckert, Martina; Angenstein, Frank; Krischek, Boris; Stavrinou, Pantelis; Timmer, Marco; et al.
Abstract: Recently, several Non- NF2 driver mutations ( KLF4, TRAF7, SMO, AKT1 E 17 K ) in meningioma have been identified. While they have been shown to correlate with certain pathological subtypes and locations, the clinical impact and repercussions on cellular pathways have largely remained elusive. Through analysis of clinical, pathological and preoperative imaging data of 96 patients and sequencing of the corresponding 96 tumor samples for the Krueppel like factor 4-K409Q mutation ( KLF4 K 409 Q ) we present evidence that the KLF4 K 409 Q tumors harbour an increased risk for peritumoral brain edema (PTBE) and can be predicted with the edema-index, a simple tool based on preoperative imaging. Further analysis involving RNA-sequencing of a matched subset of 7 KLF4 K 409 Q and 10 KLF4-wildtype ( wt ) tumors revealed a significant shift of gene expression and the upregulation of hypoxia driven pathways, including VEGF levels, in KLF4 K 409 Q tumors. On the cellular level, we go on to show that the KLF4 K 409 Q mutation results in an increased KLF-4 stability as well as the inhibition of hydroxylation dependent degradation of HIF1-α and a significant increase of VEGF expression under hypoxic conditions. Finally, we demonstrate that this upregulation of VEGF in KLF4 K 409 Q cells can be inhibited by targeting the mammalian target of rapamycin (mTor) with Temsirolimus. In summary we show that the KLF4 K 409 Q mutation in meningioma has highly relevant repercussions in both, the biological and clinical context and can be harnessed for targeted therapy.